A compact five-element printed MIMO antenna with pattern and polarization diversity for 2.45 GHz WLAN applications. Issue 11 (24th July 2022) - Chaudhari, Amar D.; Ray, K. P.
Abstract : A five-element pattern and polarization (linear/circular) diversity multiple-input-multiple-output (MIMO) antenna system has been presented in this article for application in 2.45 GHz WLAN. The proposed configuration consists of a circularly polarized (CP) patch antenna element and four monopole antenna elements placed orthogonal to each other. Broadside CP characteristics are achieved by using a square patch antenna with circular chamfered corners and central axis feed. Simple rectangular monopole antenna elements with microstrip line feed produce four linearly polarized (LP) end-fire directive radiation patterns. It achieves a bandwidth (BW) of 24.1% and 5.1% for the end-fire LP antenna element and broadside CP antenna element (corresponding axial ratio BW is 1.64%), respectively, with minimum port isolation of 15 dB. The ECC and CLL are below 0.03 and 0.5 bits/s/Hz, respectively, showing good MIMO performance. Due to its simple design, compact footprint (93 × 93 mm 2 ), planar structure, and competitive features, the proposed antenna is suited for practical WLAN applications.